Assessment of Lateralization and Handwriting Quality in Young Elementary School Students - Rada Mazić; Mile Vuković; Slađana Ćalasan (Multidisciplinarni Pristupi u Edukaciji i Rehabilitaciji, 2024)
Dominant lateralization refers to the phenomenon of having a leading extremity or leading sense during the execution of complex psychomotor activities. Writing represents a complex human ability and simultaneously the most complex form of linguistic activity, which includes knowledge, skills, and the art of proper letter formation. This study explores the relationship between lateralization and handwriting quality with the aim of identifying children with dysgraphic handwriting. The sample consisted of 90 younger elementary school students (third, fourth, and fifth grade), aged 8 to 11 years (AS = 9.93; SD = 0.84), of both genders (46 boys and 44 girls). The Handwriting Dysgraphia Assessment Test was used to assess handwriting quality. Dominant upper extremity lateralization was assessed using tests from the Sovak Test Battery (1979), while visual lateralization was assessed using a test from the General Defectology Diagnostics Practicum. The research was conducted at an elementary school in Trebinje, during February and March 2024. Research results show that a significant percentage of younger elementary school children have dysgraphic (21.1%) or severely dysgraphichandwriting (35.6%). Among the majority of participants, right-handed upper extremity dominance was observed (86.7%) along with right visual dominance (82.2%), with coordinated visual and upper extremity lateralization present in 88.9% of children. The results of investigation of the impact of uncoordinated upper extremity and visual lateralization on dysgraphic handwriting did not demonstrate statistical significance. Although our results did not confirm a link between lateralization and handwriting quality, for younger elementary school children with uncoordinated upper extremity and visual lateralization, exercises focusing on directing, practicing, and stabilizing lateralization are recommended